Analysis of Physics Laboratory Facilities and Management Standards at SMA Negeri 1 Mumbulsari - Jember - Qowasmi, Fadhiyah Nurul; Mafaza Nuris Sabeta; Alifia Aminingrum; Restu Dwi Setiyo Utami; Badriyah; Zakiya El Firdausi; Lailatul Nuraini (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was conducted to determine the standards of physics laboratory facilities and management at SMA Negeri 1 Mumbusari. This research uses descriptive research methods and a qualitative approach. The subjects of this research were laboratory managers, physics study teachers, as well as physics laboratory facilities and infrastructure at SMA Negeri 1 Mumbulsari. The collection technique is by making observations, conducting interviews with laboratory managers, and documentation. The results of the research are that SMA Negeri 1 Mumbulsari has a standard percentage of laboratory space of 67% and a standard percentage of laboratory facilities of 85% with good classification. The physics laboratory administration and management system at SMA Negeri 1 Mumbulsari is very good. So overall the physics laboratory at SMA Negeri 1 Mumbulsari has good standards of laboratory facilities and management